2023
DOI: 10.15587/1729-4061.2023.279371
|View full text |Cite
|
Sign up to set email alerts
|

Application of good manufacturing practices in the production of food products for special medical purposes

Abstract: In order to guarantee the proper quality of medical products and medicines, the mandatory application of Good Manufacturing Practices (GMP) norms in almost all countries is provided by law. Given the importance of nutritional provision of human portrebs in emergencies, the use of GMP is also relevant in the production of food products for special medical purposes. The object of research is the methodological base, approaches, and norms of GMP application in the manufacture of this product category. It is deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Taking into account the peculiarities of the functional properties of special food products, in particular for special medical purposes, when managing their safety and quality, the practice of using the norms of good manufacturing practices (GMP) is widespread [4,6,18,19]. It has been studied that the use of the prescribed GMP norms is implemented in the process of comprehensive activities aimed at ensuring compliance with safety and quality.…”
Section: Results Of Research Into the Essence Principles And Signific...mentioning
confidence: 99%
“…Taking into account the peculiarities of the functional properties of special food products, in particular for special medical purposes, when managing their safety and quality, the practice of using the norms of good manufacturing practices (GMP) is widespread [4,6,18,19]. It has been studied that the use of the prescribed GMP norms is implemented in the process of comprehensive activities aimed at ensuring compliance with safety and quality.…”
Section: Results Of Research Into the Essence Principles And Signific...mentioning
confidence: 99%
“…Further more K et al, (2021) found the importance of developing effective competency standards for GHP (Good Hygienic Practices) facilitators, especially in the context of food handling and maintaining hygiene in the work environment. In developing competency standards for GHP facilitators, emphasis is placed on the need to draw up clear and structured guidelines covering critical aspects such as knowledge of food contamination, sanitation techniques, and food safety risk management (Prytulska et al, 2023).…”
Section: Development Of Competency Standards For Ghp Facilitatorsmentioning
confidence: 99%